Comparison of Enamel Surface Integrity after De-Bracketing as Affected by Seven Different Orthodontic Residual Cement Removal Systems - Almudhi, Abdullazez; Aldeeri, Arwa; Aloraini, Abdullah Abdulrahman A.; Alomar, Ahmed Ibrahim M.; Alqudairi, Meshari Saad M.; Alzahrani, Osama Abdullah A.; Eldwakhly, Elzahraa; AlMugairin, Sarah (Diagnostics (Basel), 2023)
This study used seven different adhesive removal systems to evaluate and compare enamel surface integrity, heat generation, and time consumed during residual cement removal after de-bracketing. The sample size was 140 human premolars. Teeth were cleaned, mounted, and prepared for orthodontic bracket bonding. Brackets were then debonded using bracket-removing pliers. Teeth were randomly assigned to seven groups based on the residual cement removal system: Group 1: Stainbuster bur, Group 2: Renew diamond bur #129, Group 3: Renew carbide bur, Group 4: OneGloss Complete system, Group 5: Sof-Lex system, Group 6: Enhance Finishing and PoGo Polishing complete kit, and Group 7: Renew friction grip points. The enamel surface was evaluated for roughness before bracketing and after residual cement removal using surface profilometry. The time taken for cement removal was recorded using a digital timer, and heat generation was measured using a laser thermometer before and after cement removal. One-way ANOVA compared the pre- and post-values for enamel surface roughness, temperature, and time consumed. When comparing the difference between the post- and pre-finishing roughness using one-way ANOVA, the Renew diamond bur produced the roughest enamel surface post-removal with a mean of 4.716 μm, while the Sof-Lex recorded the lowest at 0.760 μm. The highest mean temperature was recorded with the Stainbuster bur at 5.545 °C, and the lowest temperature was recorded with the Enhance bur at 2.260 °C. The time for cement removal was the shortest with the Enhance bur at 12.2 s, whereas the time was the longest with the Renew diamond bur at 30.4 s. In conclusion, all the residual cement removal systems used in this clinically simulated study were not able to restore the original enamel surface smoothness. However, the 3M Sof-Lex produced the lowest enamel roughness but with more time consumption and heat generation. When selecting the best residual cement removal system to be used, clinicians should weigh the merits and demerits of each system based on the clinical judgement of the operator.